Pengaruh Empowering Leadership terhadap Kinerja Guru dengan Psychological Empowerment sebagai Variabel Mediasi - Yustita Damayanti (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of empowering leadership on teachers performance with psychological empowerment as a mediating variable. Research object at SMPN 1 Pacitan and SMPN 2 Pacitan. This study uses quantitative methods with a population of 101 teachers and uses a simple random sampling technique with 81 respondents. Data analysis used Structural Equation Modeling (SEM) with analysis method, namely Partial Least Square (PLS). Data processing used Smart PLS 3.0 software. The results of this study conclude that empowering leadership has a significant positive effect on teachers performance, empowering leadership has a significant positive effect on psychological empowerment, psychological empowerment has a significant positive effect on teachers performance, and psychological empowerment as a mediating variable affects the relationship between empowering leadership and teachers performance. Principals must increase the effectiveness of empowering leadership by applying high work discipline so that the psychological empowerment of teachers will also increase and have a good impact on the teacher's performance. Local government support in the provision of learning support infrastructure also needs to be improved, thus making it easier for teachers to improve the quality of teaching to students.